Participación voluntaria en políticas internacionales de cambio climático: implicancias para Chile - Montero, Juan Pablo; Cifuentes, Luis; Soto, Felipe (Estudios de Economía, 2016)
International efforts to curb greenhouse gas emissions by 2008-2012 can have implications on Chile’s economy. Although less developed countries are not asked to limit their emissions yet, they have the possibility to participate with voluntary emission reduction efforts through the clean development mechanism (CDM) and eventually other mechanisms under consideration such as voluntary country commitments (VCC). In this paper, we discuss the costs and benefits from voluntary opt-in for the case of Chile. We compare the CDM and VCC under different economic and policy scenarios, and discuss the long-term implications of today’s voluntary opt-in in the country’s future eventual obligations when its GDP per capita approaches that of some industrialized countries.